The effect of housework on wages in Germany: No impact at all - Boris Hirsch; Thorsten Konietzko (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Arbeitsmarkt- und Regionalpolitik, 2011)
This paper presents evidence on the impact of hours spent on housework activities on individuals' wages for Germany using data from both the German Socio-Economic Panel and the German Time Use Survey. In contrast to most of the international literature, we find no negative effect of housework on wages. This holds for men and women, for married and single individuals, and for part-time and full-time workers both in West and East Germany. Our insights do not change when we distinguish different types of housework activities or address the endogeneity of housework in our wage regressions by using instrumental variables estimators. – – Auf Grundlage zweier deutscher Datensätze, des Sozio-oekonomischen Panels und der Zeitbudgeterhebung, untersucht dieser Beitrag den Einfluss der für Hausarbeit aufgewandten Zeit auf die Löhne. Im Gegensatz zum Gros der internationalen Forschungsliteratur findet sich kein negativer Effekt der Hausarbeit auf die Löhne. Dieses Ergebnis zeigt sich in West- wie Ostdeutschland sowohl für Frauen und Männer, für verheiratete Individuen und Singles als auch für Teilzeit- und Vollzeitbeschäftigte. Unsere Ergebnisse ändern sich zudem nicht, wenn wir verschiedene Formen von Hausarbeit unterscheiden oder die Endogenität der geleisteten Hausarbeit in den Lohnregressionen mithilfe von Instrumentvariablenschätzungen berücksichtigen.
Keywords: J16; J31; J22; 330; housework; time use; gender pay gap; Germany